The idea of culture and the history of emotions - Petri, Rolf (Historein, 2013)
Recently, emotions have achieved a prominent place in historical research. The article tries to outline a reasonable itemisation of the three main streams in this field of study: the history of individual emotions, the study of the role that emotions have in historical processes, and the reflection about the influence of emotions on history writing. The second part addresses the methodological and theoretical status of the study of past emotions. The author criticises their definition as merely cultural phenomena, maintaining that the historian should contextualise historically the very paradigms of “culture” and “emotion”, “passion”, “sentiment”, “mood”, and the like. S/he should also better explore what emotions are, both by cross-disciplinary debate and theoretical reflection. Otherwise the history of emotions will restrict its critical potential and remain imprisoned within modernity’s canonical self-descriptions.